2020
DOI: 10.1097/ncq.0000000000000498
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of Handoff Based on the SBAR Technique on Quality of Nursing Care

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
13
0
2
Order By: Relevance
“…We excluded 6 articles judged to have critical risk of bias [18][19][20][21][22][23] (see online supplemental appendix B table 1), leaving a total of 28 articles reporting 27 studies (figure 1). These included 3 RCTs, 24-26 6 controlled before-after studies, [27][28][29][30][31][32] and 19 uncontrolled before-and-after comparisons [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] (table 1). Online supplemental appendix B table 2 presents an overview of the 28 articles, including details of the study purpose and intervention, and outcomes included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…We excluded 6 articles judged to have critical risk of bias [18][19][20][21][22][23] (see online supplemental appendix B table 1), leaving a total of 28 articles reporting 27 studies (figure 1). These included 3 RCTs, 24-26 6 controlled before-after studies, [27][28][29][30][31][32] and 19 uncontrolled before-and-after comparisons [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] (table 1). Online supplemental appendix B table 2 presents an overview of the 28 articles, including details of the study purpose and intervention, and outcomes included in the review.…”
Section: Resultsmentioning
confidence: 99%
“… 1 We noted that 32 (74.4%) of 43 nurses knew all the information to be included in the medical record when handling tracheostomized patients and fully appreciated the significant impact of bedside hand-off using the Situation, Background, Assessment, Recommendation (SBAR) technique that Abbaszade et al reported in their study. 25 Nurses should familiarize themselves with this framework to optimize communication between members of the health care team about a patient’s condition and enhance the quality of nursing care across all dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Key challenges were highlighted during the handover, and the information was handed over systematically according to the checklist, thus overcoming the problems of arbitrary conventional handover methods and ensuring the continuation of orderly nursing activities and the safety of patients. The study by Abbaszade et al ( 16 ) showed that applying the SBAR communication technique to nursing handovers could ensure the integrity of the information communicated and improve the quality of nursing. The study by Achrekar et al ( 17 ) concluded that the application of the standard SBAR technique in POC nursing handovers could improve communication between nurses and ensure the safety of patients.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been widely applied in the healthcare community and has proven its advantages in the context of nursing handovers ( 2 , 3 , 11 – 13 ). However, the lack of a standard handover checklist for use in ICU nursing settings increases the risks that may arise during the handover process to some extent ( 14 – 16 ). SBAR mode is a good shift handover mode, which can provide comprehensive, accurate and systematic information and avoid the above shortcomings.…”
Section: Introductionmentioning
confidence: 99%